Historically-geographical aspects of settlement of population in the basin of the Ural River within the West Kazakhstan region. (Journal of Geography and Environmental Management, 2016)
This article analyzes the modern settlement of population in the basin of the Ural River within the West Kazakhstan region. The paper deals with the history of settlement of the study area, differences in crowded settlementsand right banks of the left bank of the river basin. The author identifies factors affecting the system of settling in the basin of the Urals, as well as distinctive similarities placement of settlements and their crowded study area.